Brain correlates of urban environmental exposures in cognitively unimpaired individuals at increased risk for Alzheimer's disease: A study on Barcelona's population - Carles Falcón; Mireia Gascon; José Luis Molinuevo; Grégory Operto; Marta Cirach; Xavier Gotsens; Karine Fauria; Eider M. Arenaza‐Urquijo; Jesús Pujol; Jordi Sunyer; Mark J. Nieuwenhuijsen; Juan Domingo Gispert; et al. (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2021)
Abstract Introduction Urban environmental exposures might contribute to the incidence of Alzheimer's disease (AD). Our aim was to identify structural brain imaging correlates of urban environmental exposures in cognitively unimpaired individuals at increased risk of AD. Methods Two hundred twelve participants with brain scans and residing in Barcelona, Spain, were included. Land use regression models were used to estimate residential exposure to air pollutants. The daily average noise level was obtained from noise maps. Residential green exposure indicators were also generated. A cerebral 3D‐T1 was acquired to obtain information on brain morphology. Voxel‐based morphometry statistical analyses were conducted to determine the areas of the brain in which regional gray matter (GM) and white matter (WM) volumes were associated with environmental exposures. Results Exposure to nitrogen dioxide was associated with lower GM volume in the precuneus and greater WM volume in the splenium of the corpus callosum and inferior longitudinal fasciculus. In contrast, exposure to fine particulate matter was associated with greater GM in cerebellum and WM in the splenium of corpus callosum, the superior longitudinal fasciculus, and cingulum cingulate gyrus. Noise was positively associated with WM volume in the body of the corpus callosum. Exposure to greenness was associated with greater GM volume in the middle frontal, precentral, and the temporal pole. Discussion In cognitively unimpaired adults with increased risk of AD, exposure to air pollution, noise, and green areas are associated with GM and WM volumes of specific brain areas known to be affected in AD, thus potentially conferring a higher vulnerability to the disease.